Structural and biochemical study of Candida albicans polarisomal proteins - Loh, Zhi Yang (Nanyang Technological University, 2021)
The polarisome is a multi-protein complex involved in the assembly of actin cytoskeleton during polarised hyphae growth in pathogenic yeast C. albicans. In this thesis, we present the crystal structure of C. albicans polarisomal protein Aip5 (786-896) at 2.65 Å resolution. Structural comparison of nucleation promoting factor Aip5 with its S. cerevisiae homolog revealed the difference in actin-binding loop flexibility, which may account for their differential actin-binding affinities reported in literature.